FUNGSI SOSIAL ATURAN BERPAKAIAN DI SEKOLAH ISLAM DALAM PERSPEKTIF SOSIOLOGI PENDIDIKAN - Umam, Choirul; Putri Nabila, Vania; Maimunah, Siti; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2026)
Dress codes in Islamic schools are commonly understood as religious regulations aimed at instilling modesty and moral compliance among students. Such an understanding tends to frame dress codes as individual moral obligations, thereby overlooking their broader social and structural dimensions. This article aims to analyze the social functions of dress codes in Islamic schools from the perspective of the sociology of education. Employing a qualitative-descriptive literature review, this study examines scholarly journal articles, sociological theories, and publicly accessible policy documents from Islamic schools. The findings indicate that dress codes function as mechanisms of bodily discipline, symbols of collective identity formation, and instruments of social control institutionalized within educational systems. Furthermore, dress codes contribute to the reproduction of power relations and social structures through standards of appearance, symbolic representations, and sanction systems. This article argues that dress codes in Islamic schools should not be understood merely as religious norms, but as social practices embedded within the broader project of modern Islamic education.